Framework for Furniture and Wood Processing Industry Polytechnic in Era Disruption of Covid-19 - Fesa Putra Kristianto; Nuthqy Fariz; Deni Saputra; Salwa Islami Athirah (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2021)
In the era of the Covid-19 pandemic, all activities are forced to adapt to theDisruption Era, one of which is the education sector. The era of Disruption Covid-19 changed the learning system from face to face to online and did not change the quality of the learning process. Therefore, the Furniture and Wood Processing Industry Polytechnic must create a new framework in order to survive. This study aims to create a new framework that has the perspectives of various stakeholders such as government, industry, academic institutions, certification institutions, students and technological developments. The making of this framework is based on PEST analysis and a drives competitive for universities according to (Panday, 2014). The result of the framework for the Wood Furniture and Processing Industry Polytechnic are implementation health protocol for Covid-19, improvement of facilities dan infrastructure, creating income from teaching factory, SDM adaptation for improvement facilities and infrastructure, and quality assurance of graduates. The next step is to carry out monitoring and evaluation (MONEV) so that the implementation of framework runs according to the references and targets. https://doi.org/10.21632/irjbs.14.2.107-117